SILEK HARIMAU BANDAROLOBIAH KAMPUNG PARAMAN KABUPATEN PASAMAN - Wahyu Saputra, Adi; Sasmitha, Weny; Suwirman; Asnaldi, Arie (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify the movements, steps, and techniques of Silek Harimau Bandarolobiah in Kampung Paraman, Pasaman Regency, as an effort to support the existence and preservation of Minangkabau traditional martial arts (Silek). The study was motivated by the declining interest of younger generations in traditional martial arts, an unoptimized coaching system, and the absence of systematic documentation of the movements, steps, and techniques of Silek Harimau Bandarolobiah as a local cultural heritage. This study employed a qualitative approach with a descriptive design, conducted in Kampung Paraman, Nagari Cubadak Timur, Pasaman Regency. Data were collected through passive participant observation, semi-structured interviews with four informants (a Tuo Silek, the Wali Nagari, a martial arts practitioner, and a customary leader), and documentation, then analyzed using Spradley's domain, taxonomic, componential, and thematic analysis, with validity tested through source and method triangulation. The results show that Silek Harimau Bandarolobiah features distinctive tiger-inspired movements, including a low stance (duduak randah), dynamic body movements (gelek, agah, and tiger mimicry), defensive techniques (tangkok and elakan berisi), and offensive techniques (sapu, guntiang, and caka), all grounded in the philosophy of adat basandi syarak, syarak basandi Kitabullah. Systematic documentation is concluded to be a strategic step for the sustainable preservation of this martial art.